The Economy of Energy Conservation in Educational Facilities. A Report. Revised Edition - Educational Facilities Labs., Inc., New York, NY.; Educational Facilities Labs., Inc., New York, NY. ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
This is an update of the 1973 edition of a guide for energy conservation in schools. This Educational Facilities Laboratories publication is an information source for teachers, school administrators, school maintenance personnel, school designers, or anyone interested in conserving energy in schools. Topics discussed include: (1) life-cycle costing; (2) establishing an energy management program; (3) changes in operation and maintenance practices; (4) modernizing existing schools; (5) waste-heat recovery; (6) insulation; (7) solar applications in existing schools; (8) new school design needs; and (9) solar energy uses in new schools. A summary and recommendations are also provided. (MR)
Availability: Educational Facilities Laboratories, 850 Third Avenue, New York, NY 10022 ($4.00).
ERIC Note: For related document, see ED 082 321; Not available in hard copy due to copyright restrictions.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Guides; Building Design; Building Operation; Climate Control; Design Requirements; Educational Environment; Energy; Energy Conservation; Facility Improvement; Life Cycle Costing; School Administration; School Buildings; Guides, Non-Classroom.